Harmonizing Two of History Teaching's Main Social Functions: Franco-Québécois History Teachers and Their Predispositions to Catering to Narrative Diversity - Paul Zanazanian; Sabrina Moisan (MDPI AG, 2012)
This article presents the Quebec ministry of education's (MELS) strategy for diversifying the national historical narrative that is transmitted in the province's History and Citizenship Education program as well as the manner in which Francophone national history teachers put this strategy into practice. In bringing research on their social representations and historical consciousness together, this paper looks at some of the main challenges that these teachers face when specifically harmonizing two of history teaching's central social functions for catering to narrative diversity. When seeking to adequately balance the transmission of a national identity reference framework with the development of autonomous critical thinking skills, it becomes clear that these teachers' general quest for positivist-type, true and objective visions of the past as well as their overall attachment to the main markers of their group's collective memory for knowing and acting Québécois impede them from fully embracing the diversification of the province's historical narrative. The article ends by raising some important questions regarding the relevance of assisting teachers to authentically develop their own voice and vision for harmonizing the two aforementioned functions of history teaching and for being answerable to the decisions they make when articulating and acting upon such beliefs in class.